Model Pengembangan Kurikulum PAI di MTsS Al-muslim Peusangan - Mahmudi Mahmudi; Raiyan Raiyan; Syakbi Syakbi (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2023)
The development of the Islamic Religious Education curriculum in general educationfocuses more on cognitive aspects than affective and psychomotor aspects, while at theAmuslim Integrated Islamic Boarding School the development does not only focus oncognitive aspects but also on affective and psychomotor aspects. This study aims todetermine the model of PAI curriculum development at MTsS Almuslim, theimplementation of the PAI curriculum at MTsS Al-Muslimand the inhibiting andsupporting factors in developing the PAI curriculum at MTsS Almuslim. In this study,the researcher used the type of research, namely qualitative research with the formulationof the problem, namely how to model the development of the PAI curriculum at MTsSAlmuslim? How is the implementation of the PAI curriculum at MTsS Almuslim? Whatare the inhibiting and supporting factors in MTsS Almuslim? The results of the researchare: First, the model of curriculum development for Islamic Religious Education atMTsS Al-Muslimuses the Darussalam Gontor curriculum model which is modified withthe Al-MuslimIntegrated Islamic Boarding School curriculum model. Second, theimplementation of the field of study in Islamic Religious Education at MTsS Al-Muslimisvery dependent on the sincerity of the teacher, the ability of the teacher to deliver thematerial, the ability to choose and apply learning methods, and utilize existing mediatools for successful learning. The implementation has also been divided into 3 forms ofimplementation such as the implementation of the Hafiz Qur'an Program,Implementation of Islamic Religious Education subjects in the classroom and outsidethe classroom (Extracurricular) such as Tajiyiz mayit, congregational prayers, sunnahfasting, performing Hajj, commemorating major holidays. Islam. Third, regarding thesesupporting and inhibiting factors at MTsS Almuslim, if you look at the supportingfactors at MTsS Almuslim, it is very supportive in terms of needs such as media tools,comfortable classroom conditions, very strategic places, students living in the school environment. If you look at the inhibiting factors, it is only the student sector who getstired easily due to the ineffective use of time. Keywords: Curriculum, Islamic Religious Education (PAI), Islamic Boarding School